Training on Identification of Hazardous Food Preservatives and Utilization of Chitosan as A Natural Preservative - Marianti, Aditya; Christijanti, Wulan; Dimarti, Safira Chairani; Wardani, Agata Iswiana Diah; Maulana, Silvia Faori; Tsaniyah, Nurotun Najmatus (Universitas Negeri Semarang, 2023)
Food preservation with borax and formaldehyde is still widely practiced. The use of borax and formaldehyde as food preservatives has a negative impact on health. Knowledge and skills to identify borax and formaldehyde content using simple, cheap, and easy techniques need to be trained. A simple technique for testing borax uses the turmeric method, while formaldehyde uses young papaya sap. The public also needs to be given an alternative, safe way of preserving food with chitosan. Participatory methods were used in this activity. The activity stages begin with preparation and socialization, training, monitoring, and evaluation. The activity was attended by 23 people on the first day and 17 people on the second day, including cadres of the FKK, PKK, Karang Taruna, Elderly Forum, LPMK, and culinary UKM. There was a significant increase in the knowledge of training participants with an N gain of 0.58, including the moderate or quite effective category. Participants also responded positively. Participants have the skills to detect borax using the turmeric method and formaldehyde using papaya sap. Training participants are also skilled in using liquid chitosan as a natural food preservative. The conclusion of this activity is that the training participants increased their knowledge about dangerous food preservatives, had the skills to detect borax and formaldehyde in food ingredients with simple technology, and applied liquid chitosan as a natural preservative.